A Survey on Quality of Work-life of Employees (International Journal of Innovative Research in Engineering & Management, 2021)
Workplace quality is a crucial notion that plays an important roles in employee’s lives. For all businesses to continue to  recruit and retain employees, high quality of work-life (QWL)  is required. The purpose of this study was to discover the  elements the work-life quality of employees in privately limited enterprises. Employee opinions on statements on the QWL elements can be used to measure an organization's  Work-life Quality. Employees to report greater levels of  performance and job participation if they believe a company  provides them with high-quality work in exchange for their  effort. Employee satisfaction promotes improved performance  as well as greater acquisition and retention of top talent,  increasing the organization's capacity. Purpose was to look at  working for private organizations. In future factors of quality  of work-life must be implemented by the organization in order  to obtain more output as well as to increase employee’s  loyalty and dedication towards the organization.
Keywords: Company; Employee; Life; Organization; Quality; Work